Effect of Anatomical Customization of the Fiber Post on the Bond Strength of a Self-Adhesive Resin Cement - Adricyla Teixeira Rocha; Leticia Machado Gonçalves; Ana Júlia de Carvalho Vasconcelos; Etevaldo Matos Maia Filho; Ceci Nunes Carvalho; Rudys Rodolfo De Jesus Tavarez (International Journal of Dentistry)
Aim. The aim of the study was to evaluate, by means of the push-out test, the effect of the anatomical customization of the fiber post on the bond strength of a self-adhesive resin cement. Methods. Twelve endodontically treated, human, upper central incisors were randomly divided into two groups (n=6): control (glass fiber posts cemented with Relyx® U200) and customized (glass fiber posts anatomically customized with translucent composite resin cemented with Relyx U200). The roots were sectioned into three slices, cervical, middle, and apical, and photographed with a digital camera attached to a stereomicroscopic loupe. The images were analyzed by software, for evaluation of the cement line. The slices were subsequently submitted to the push-out test until the post had completely extruded, and the fracture mode was analyzed with a stereomicroscopic loupe. Results. The results showed significant differences between the groups in the different root thirds in relation to the area occupied by air bubbles (p<0.05). Bond strength, when all the thirds are considered, was 8.77 ± 4.89 MPa for the control group and 16.96 ± 4.85 MPa for the customized group. Conclusion. The customized group showed greater bond resistance than the control group and a more uniform cement layer.